Determination of total extractives and cellulose content of Ipe wood submitted to thermal modification process (Revista de Ciências Agroveterinárias, 2023)
The demand for products from wood has been expanding, because of this, there is a need for studies related to the quality and application of these materials. Thus, the present research aimed to evaluate the extractive and cellulose content of Ipê wood submitted to the thermal modification process. To carry out the study, four individuals of Handroanthus chrysotrichus (Mart. ex DC.) Mattos, 11 years old, were slaughtered. Subsequently, samples measuring 2.5 x 2.5 x 41 cm were prepared and placed in an oven with forced air circulation, at temperatures of 120, 150, 180 and 210 ºC, for a period of 4 h. Then, random portions of the specimens were sectioned and ground in a knife mill, and then, sieved in the 40/60 mesh fraction, to carry out the chemical tests of total extractives and cellulose content. The data were processed and submitted to the Tukey average test, using the R software. The results of the chemical properties studied indicated variations according to the temperatures, not showing a stabilization trend between the treatments applied. A relationship between the behavior of these properties and the other technological characteristics of the works available in the literature was observed. In general, further studies are recommended on the chemical properties of wood of this species associated with the application of high temperatures.
Keywords: extractives content; cellulose content; thermal treatment; Handroanthus chrysotrichus; cellulose